2017
DOI: 10.3390/ijms19010093
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27b Depletion Enhances Endotrophic and Intravascular Lipid Accumulation and Induces Adipocyte Hyperplasia in Zebrafish

Abstract: miR-27b has emerged as a regulatory hub in cholesterol and lipid metabolism, and as a potential therapeutic target for treating atherosclerosis and obesity. However, the impact of miR-27b on lipid levels in vivo remains to be determined. Zebrafish lipids are normally stored as triacylglycerols (TGs) and their main storage sites are visceral, intramuscular, and subcutaneous lipid depots, and not blood vessels and liver. In this study, we applied microRNA-sponge (miR-SP) technology and generated zebrafish expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
(100 reference statements)
1
21
0
1
Order By: Relevance
“…Among the known miRNAs identified, we found that the expression of miRNAs is consistent with the previous results, such as miR-146b, miR-130a, miR-27b-5p, and miR-30a. Studies have shown that overexpression of miR-146b promotes 3T3-L1 cell differentiation [26] and human visceral adipocyte differentiation [27], overexpression miR-130a in porcine preadipocytes can inhibit its differentiation [28], and the depletion of miR-27b promotes lipid accumulation and weight gain in zebrafish [29]. In addition, most abundantly expressed miRNAs, such as miR-30a and miR-106, have been reported that inhibition of miR-30a can promote adipocyte differentiation [30] and miR-106 as negative regulators of adipocyte differentiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Among the known miRNAs identified, we found that the expression of miRNAs is consistent with the previous results, such as miR-146b, miR-130a, miR-27b-5p, and miR-30a. Studies have shown that overexpression of miR-146b promotes 3T3-L1 cell differentiation [26] and human visceral adipocyte differentiation [27], overexpression miR-130a in porcine preadipocytes can inhibit its differentiation [28], and the depletion of miR-27b promotes lipid accumulation and weight gain in zebrafish [29]. In addition, most abundantly expressed miRNAs, such as miR-30a and miR-106, have been reported that inhibition of miR-30a can promote adipocyte differentiation [30] and miR-106 as negative regulators of adipocyte differentiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…In order to illustrate the mechanism of the effect of hypoxic exercise on blood lipid, this study observed the changes of miR-27b expression on blood lipids in obese rats with hypoxic exercise. MiR-27b was recently reported to be a key regulator of cholesterol and lipid metabolism ( Hsu et al, 2018 ). In obese people, elevated miR-27 levels in the blood have been associated with higher TG and LDL-C levels and lower HDL-C levels ( Can et al, 2016 ); moreover, it has been suggested that miR-27b can accelerate the development of arteriosclerosis by reducing the expression of PPARγ, thereby inducing perivascular adipose tissue hypertrophy ( Chen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-27b can bind the 3′UTR of PPARγ mRNA and suppress its expression ( McGregor and Choi, 2011 ). Meanwhile, PPARγ can regulate the expression of a series of lipid metabolism-related genes, including cholesterol 7 alpha-hydroxylase ( CYP7A1 ), fatty acid translocase 36 ( CD36 ), heart-type fatty acid-binding protein ( H-FABP ), fatty acid transport protein ( FATP ), adipose triglyceride lipase ( ATGL ), and lipoprotein lipase ( LPL ) ( Zhu et al, 2015 ; Hsu et al, 2018 ; d’Angelo et al, 2019 ; Xu et al, 2019 ). Interestingly, both hypoxia and exercise have been reported to modulate the expression levels of miR-27b and PPARγ ( Park and Park, 2012 ; Sutliff et al, 2013 ; Tomaz et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that miR-27b is down-regulated in in vitro cultured adipocytes and adipose tissue in obesity-related models and that miR-27b impairs adipocyte differentiation in 3T3-L1 cells and human adipose-derived mesenchymal stem cells via its associations with PPARγ and C/EBPα [24][25][26][27]. In zebrafish, depletion of miR-27b has shown increases in PPARγ, C/EBPα, and SREBP-1c, resulting in the enhancement of adipocyte hyperplasia [28]. In addition to these regulators, miR-27b negatively regulates lysyl oxidase and other genes involved in adipocyte differentiation [29].…”
Section: Discussionmentioning
confidence: 99%